Mayer-Rokytansky-kuster-Hauser Syndrome: A Rare Congenital Anomaly-Report of Two Cases - Parvin, Roksana; Begum, Suraiya; Akhter, Romana; Sharmin, Farzana (Bangladesh Journal of Child Health, 2021)
Mayer -Rokytansky-Kuster- Hauser Syndrome (MRKH) is a rare congenital anomaly, in which derivatives of mullerian duct is partially or completely absent whereas ovaries are normally present in a female patient. The patients usually present to physician with primary amenorrhea in adolescent period, when secondary sexual characteristics develops normally.Surgical correction permits normal sexual function and, possibly, reproduction with assisted techniques in MRKH patients. So,early diagnosis is very important to offer possible treatment options to the parents and patients and also to avoid psychological impact on patient. Here, we have described two cases of MRKH with different presenting complaints. BANGLADESH J CHILD HEALTH 2021; VOL 45 (1) : 48-50